Immunostimulation by Synthetic Lipopeptide-Based Vaccine Candidates: Structure-Activity Relationships - Zaman, Mehfuz; Toth, Istvan (Frontiers in Immunology, 2013)
Peptide based vaccines offer several advantages over conventional whole organism or protein approaches by offering improved purity and specificity in inducing immune response. However, peptides alone are generally non-immunogenic. Concerns remain about the toxicity of adjuvants which are critical for immunogenicity of synthetic peptides. The use of lipopeptides in peptide vaccines is currently under intensive investigation because potent immune responses can be generated without the use of adjuvant (thus are self-adjuvanting). Several lipopeptides derived from microbial origin, and their synthetic versions or simpler fatty acid moieties impart this self-adjuvanting activity by signalling via Toll-like receptor 2 (TLR2). Engagement of this innate immune receptor on antigen-presenting cell leads to the initiation and development of potent immune responses. Therefore optimization of lipopeptides to enhance TLR2-mediated activation is a promising strategy for vaccine development. Considerable structure-activity relationships that determine TLR2 binding and consequent stimulation of innate immune responses have been investigated for a range of lipopeptides. In this review we address the development of lipopeptide vaccines, mechanism of TLR2 recognition, and immune activation. An overview is provided of the best studied lipopeptide vaccine systems.